Bidirectional regulatory effects of Cordyceps on arrhythmia: Clinical evaluations and network pharmacology - Wang, Lijuan; Sun, Helin; Yang, Meina; Xu, Yulin; Hou, Linlin; Yu, Haomiao; Wang, Xueyin; Zhang, Zhongwen; Han, Jinxiang (Frontiers in Pharmacology, 2022)
Background: Cordyceps is a precious Chinese herbal medicine with rich bio-active ingredients, which is used for arrhythmia alongside routine treatment. However, the efficacy and potential mechanisms of Cordyceps on patients with arrhythmia remain unclear. Methods: Randomized controlled trials about bradycardia treatment with Cordyceps were searched through diverse databases and available data. Dichotomous variables were expressed as risk ratio (RR) with 95% confidence interval (CI). Continuous variables were expressed as standardized mean difference (SMD) with 95% CI. Network pharmacology was used to identification of potential targets of Cordyceps for arrhythmia. Metascape was used for Gene Ontology (GO) and Genomes (KEGG) pathway enrichment analysis. Results: 19 trials included 1,805 patients with arrhythmia, of which 918 patients were treated with Ningxinbao capsule plus routine drugs and 887 patients were treated with only routine drugs as the control. 6 trials reported bradycardia and the other 13 trials reported tachycardia. Treatment with Cordyceps significantly improved total effective rate in bradycardia (RR=1.24; 95% CI, 1.15 to 1.35; Pz<0.00001) and tachycardia (RR=1.27 ; 95% CI, 1.17 to 1.39; Pz<0.00001). Cordyceps also had beneficial effects on secondary outcomes. No serious adverse events occurred in patients treated with Cordyceps. The results of KEGG pathway enrichment analysis were mainly enriched in adrenergic signaling in Cardiomyocytes and PI3K-Akt signaling pathway. IL6, TNF, TP53, CASP3, CTNNB1, EGF and NOS3 might be the key targets for Cordyceps in the treatment of arrhythmia. Conclusions: This study clarified that Cordyceps has a certain positive effect on the treatment of arrhythmia and its main mechanism may be through the regulation of the adrenergic signaling in Cardiomyocytes and PI3K-Akt signaling pathway.